Multiplicity dependence of charged-particle intra-jet properties in pp collisions at √s = 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Kroesen, Martin; et al. (The European physical journal. C, Particles and fields, 2024)
The first measurement of the multiplicity dependence of intra-jet properties of leading charged-particle jets in proton-proton (pp) collisions is reported. The mean charged-particle multiplicity and jet fragmentation distributions are measured in minimum-bias and high-multiplicity pp collisions at center-of-mass energy √ s = 13 TeV using the ALICE detector. Jets are reconstructed from charged particles produced in the midrapidity region |eta| < 0.9 using the sequential recombination anti-kTalgorithm with jet resolution parameters R = 0.2, 0.3, and 0.4 for the transverse momentum (pT) interval 5-110 GeV/c. The high-multiplicity events are selected by the forward V0 scintillator detectors. The mean charged-particle multiplicity inside the leading jet cone rises monotonically with increasing jet pT in qualitative agreement with previous measurements at lower energies. The distributions of jet fragmentation function variables z ch and xi ch are measured for different jet -pT intervals. Jet -pT independent fragmentation of leading jets is observed for wider jets except at high- and low-z ch values. The observed “hump-backed plateau” structure in the xi ch distribution indicates suppression of low-pT particles. In high-multiplicity events, an enhancement of the fragmentation probability of low-z ch particles accompanied by a suppression of high-z ch particles is observed compared to minimum-bias events. This behavior becomes more prominent for low-pT jets with larger jet radius. The results are compared with predictions of QCD-inspired event generators, PYTHIA 8 with Monash 2013 tune and EPOS LHC. It is found that PYTHIA 8 qualitatively reproduces the jet modification in high-multiplicity events except at high jet pT. These measurements provide important constraints to models of jet fragmentation.